Linking MIS Utilization to Pensioners’ Satisfaction Through Service Quality - Rozanna, Mira (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study examines the effect of Management Information System (MIS) utilization on pensioners’ satisfaction through the mediating role of service quality within the Taspen public pension institution in Indonesia. The research aims to clarify how digital system adoption contributes to perceived service performance and satisfaction outcomes. A quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) was applied to analyze data from 332 pensioners collected through structured questionnaires. The SmartPLS 3 software was used to test both direct and indirect relationships among constructs. The findings reveal that MIS utilization significantly improves service quality but has no direct impact on pensioners’ satisfaction. Service quality fully mediates the relationship, indicating that pensioners experience satisfaction only when system use enhances the quality-of-service delivery. The study employs a cross-sectional design, which limits causal interpretation over time. Future research should adopt longitudinal or comparative approaches to validate the generalizability of the model across institutions. This study contributes to e-government and information system literature by empirically confirming service quality as the mechanism linking digital system utilization and satisfaction in public pension services. It provides practical insight for policymakers to align digital transformation initiatives with service excellence strategies.